2015
DOI: 10.1186/s12934-015-0322-5
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic fingerprinting of Lactobacillus paracasei: the optimal quenching strategy

Abstract: BackgroundQuenching in cold buffered methanol at −40 °C has long been the preferred method for sub-second inactivation of cell metabolism during metabolic fingerprinting. However, methanol is known to cause intracellular metabolite leakage of microbial cells, making the distinction between intra- and extracellular metabolites in microbial systems challenging. In this paper, we tested three quenching protocols proposed for microbial cultures: fast filtration, cold buffered methanol and cold glycerol saline.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Villas-Boas and Bruheim [ 85 ] reported that cold glycerol-saline (3 : 2) showed much higher intracellular metabolite recovery in Pseudomonas fluorescens compared to cold methanol. A similar finding showed that cold glycerol-saline only caused minimal cell damage towards Lactobacillus paracasei [ 84 ]. Chen et al [ 91 ] demonstrated that the use of methanol/glycerol (−20°C) successfully recovered and identified a high concentration of intracellular metabolites in Lactobacillus bulgaricus .…”
Section: Sample Preparation Methods For Bacterial Metabolitessupporting
confidence: 60%
See 2 more Smart Citations
“…Villas-Boas and Bruheim [ 85 ] reported that cold glycerol-saline (3 : 2) showed much higher intracellular metabolite recovery in Pseudomonas fluorescens compared to cold methanol. A similar finding showed that cold glycerol-saline only caused minimal cell damage towards Lactobacillus paracasei [ 84 ]. Chen et al [ 91 ] demonstrated that the use of methanol/glycerol (−20°C) successfully recovered and identified a high concentration of intracellular metabolites in Lactobacillus bulgaricus .…”
Section: Sample Preparation Methods For Bacterial Metabolitessupporting
confidence: 60%
“…Studies have reported that quenching process can be performed before, during, or after harvesting of sample [ 36 , 49 , 58 , 80 82 ]. The step is essential to “quench” or stop or at least slow down the turnover rate and in vivo metabolic reactions [ 30 , 67 , 83 , 84 ]. Quenching is done by exposing the sample to solvent at either extreme temperatures (cold and hot) [ 24 , 52 , 75 ] or extreme pH conditions (highly acidic or alkaline) [ 13 , 30 , 68 ].…”
Section: Sample Preparation Methods For Bacterial Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the original version of this article [ 1 ] contained an error within the abstract. The sentence beginning with “Membrane integrity assayed by propidium iodide” reads “approximately 10 % of the L. paracasei cell membranes were damaged” but should read “approximately 100 % of the L. paracasei cell membranes were damaged”.…”
Section: Erratum To: Microb Cell Fact (2015) 14:132 Doi 101186/s1293mentioning
confidence: 99%
“…As an alternative, a fast filtration system combined with quenching/extraction has been proposed as an effective strategy to reduce the loss of intracellular metabolites ( 20 ). However, performing manual fast filtration and clogging of filters are inevitable drawbacks of this approach ( 21 , 22 ). Alternative quenching strategies that reduce the leakage of intracellular metabolites and stabilize bacterial cells have been tested with limited success, including using different methanol concentrations ( 14 ), addition of buffering solutions ( 13 , 23 , 24 ), and changing the ratios of bacterial culture to quenching solvents.…”
Section: Introductionmentioning
confidence: 99%